The direct method and multilingual turn in teaching Japanese as a foreign language - Luchenko, Olha; Kovinko, Karina (Educational Challenges, 2025)
Purpose. The purpose of the article is to investigate the beliefs of Japanese native-speaker teachers (NSTs) regarding the direct method of teaching in the context of Japanese as a foreign language (JFL). The study aims to explore both the positive and negative perceptions of NSTs concerning this teaching approach, particularly in light of the shift towards more multilingual strategies in language education. Methodology. A global survey was conducted among 256 NSTs from 39 countries through Japanese language institutions spanning all educational stages. Data were collected over six months via a Japanese-language questionnaire administered through Google Forms. The survey included both closed and open-ended questions to gather quantitative and qualitative insights on teachers’ perceptions of the direct method. Statistical analysis involved descriptive statistics for closed question responses and qualitative content analysis for open-ended answers, identifying recurring themes. Results. Teachers identified key advantages of the direct method, including increased exposure to Japanese, alignment of instructional and target language, and fostering an immersive learning environment. However, significant challenges were also reported, such as difficulties in verifying comprehension, teaching abstract concepts, and maintaining student motivation. Additional concerns included the method’s time-intensive nature, the high cognitive burden for beginners, and its limited applicability in mixed-proficiency classrooms. Conclusions. Differences in teaching contexts across countries influence NSTs’ adoption of the direct method, leading to an emphasis on balancing it with more structured approaches to cater to diverse learner profiles. Given the increasing multilingual nature of classrooms, a balanced instructional strategy that integrates the direct method with selective use of students’ native language or English may offer a more effective framework for JFL instruction, particularly in international settings.